Mapped In or Mapped Out? The Romanian Poor in Inter-household and Community Networks - Amelina, Maria; Chiribuca, Dan; Knack, Stephen (Washington, DC: World Bank, 2013)
This paper analyses patterns of economic and social interactions that sustain the poor or, alternatively, isolate them yet further from other households, from the communities in which they live and, by extension, from social networks and economic opportunities. The study also assesses interactions of the poor with local and central government in terms of the level of trust and satisfaction with public officials, the level of involvement in public actions and public decision-making and the ability of local governments to respond to the needs of their poorer constituency, especially in providing social assistance and other Minimum Income Guarantee benefits.